Professional Access 2013 programming - Hennig, Teresa (Wrox programmer to programmer, 2013)
Authoritative and comprehensive coverage for building Access 2013 Solutions Access, the most popular database system in the world, just opened a new frontier in the Cloud. Access 2013 provides significant new features for building robust line-of-business solutions for web, client and integrated environments. This book was written by a team of Microsoft Access MVPs, with consulting and editing by Access experts, MVPs and members of the Microsoft Access team. It gives you the information and examples to expand your areas of expertise and immediately start to develop and upgrade projects. * Explores the new development environment for Access web apps * Focuses on the tools and techniques for developing robust web applications * Demonstrates how to monetize your apps with Office Store and create e-commerce solutions * Explains how to use SQL Server effectively to support both web and client solutions * Provides techniques to add professional polish and deploy desktop application * Shows you how to automate other programs using Macros, VBA, API calls and more. Professional Access 2013 Programming is a complete guide on the latest tools and techniques for building Access 2013 applications for both the web and the desktop so that developers and businesses can move forward with confidence. Whether you want to add expand your expertise with Client/Server deployments or start developing web apps, you will want this book as a companion and reference.